(untitled) - Woodson, R. Dodge (New York, N.Y.,London, 2005)
This book includes: full coverage of estimating; takeoffs; job-simplifying; fast code facts; and sensible shortcut tip boxes. It is great for designing and estimating projects. It includes ready-to-run solutions for plumbing and pipefitting, and instant results. Packed with charts and tables that allow readers to quickly look up time-saving answers, this handy tool is a ready source of commonly used calculations, formulas, and, best of all, solutions. In addition to easy-to-find answers, this guide delivers: a concise outline of trade mathematics; plastic and copper pipe and copper tubing facts and figures; standard and handicapped fixture layouts; guidelines for sizing water heaters; potable water standards; equipment weight load standards; friction tables; and relevant electrical factors.Suitable for designing and estimating projects, this manual will prove to be invaluable. A great productivity booster, it will assist in delivering prompt, on-target, and even on-the-spot estimates. It features 'Look-It-Up Calculations' for: pipe fitting; fabrication and layout; fixture-units; vent systems; drains and sewers; combination waste and vent systems; piping offsets; thermal efficiency; and more!
Keywords: Plumbing,Engineering mathematics,Hệ thống ống nước,Kỹ thuật toán học; Mathematics,Formulae,Toán học,Công thức